Factors contributing to practitioner choice when declining involvement in legally available care: A scoping protocol. Issue 8 (17th August 2018) - Brown, Janine; Goodridge, Donna; Thorpe, Lilian; Chipanshi, Mary
Abstract : Introduction: As legislation addressing medical treatments continues to evolve, there are several circumstances (eg, abortion, assisted dying) in which health practitioners may choose to not provide legally available care options. It is not always clear what underlies practitioner choice, as some research has suggested non-participation in care provision is not always due to an ethical abstention but may represent other factors. This results in tension between a practitioner's right to refrain from practices deemed morally objectionable by the practitioner, and the care recipient's right to access legally available treatments. The aim of this systematic scoping review is to identify the current knowledge regarding all the factors influencing practitioner's choices when declining involvement in legally available healthcare options. Methods and analysis: Arksey and O'Malley's scoping framework in concert with Levac et al 's enhancements will guide the systematic scoping review methodological processes. English language documents from 1 January 1998 to current will be sought using Medline, CINAHL, JSTOR, EMBASE, ProQuest Dissertations and Theses Global, PsychINFO and Sociological Abstracts. MeSH headings, keywords and synonyms will be adjusted using an iterative search process. Theses and dissertations will be included in the search protocol; however, other grey literature will be accessed only as required. Two research team members will screen the abstracts and full articles against inclusion criteria. Article information will be extracted via a data collection tool and undergo thematic analysis. Descriptive summary (visual summary and study contextual information) and a presentation of analytical themes will align findings back to the research question. Ethics and dissemination: Ethics approval is not required. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist will be used to support transparency and guide translation of findings. Findings will be disseminated through professional networks, in peer-reviewed journals and conferences via abstract and presentation.